Reversing the Gaze: Alicia Berenson’s Final Act of Resistance in The Silent Patient - Alfira Amalia Latif; Muizzu Nurhadi; Erika Citra Sari Hartanto (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines how Alicia Berenson responds to the power relations exercised by Theo Faber in Alex Michaelides’s The Silent Patient (2019). The research problem arises from the tendency to view subordinate characters within clinical institutions as entirely passive, whereas Michel Foucault’s notion of power relations always leaves room for resistance. This study aims to identify the forms of Alicia’s responses to the institutional, epistemic, and disciplinary control exercised over her by Theo. Using a qualitative descriptive method, data in the form of narrative excerpts, dialogues, and diary entries were collected and analysed through Foucault’s concepts of institutional power, power-knowledge, discipline and surveillance, and resistance. The findings show that Alicia’s responses develop in four forms: her sustained silence as an active refusal to be extracted, her diary and painting as alternative spaces of expression that resist clinical classification, her direct confrontational acts that momentarily reverse the observing and observed positions, and her final disclosure of knowledge that reverses the informational asymmetry between her and Theo. The study concludes that although none of these responses fully dismantles the power structures confining her, their presence demonstrates that a dominated subject retains agency within power relations.